2009
DOI: 10.1007/s10711-009-9437-3
|View full text |Cite
|
Sign up to set email alerts
|

Profinite properties of graph manifolds

Abstract: Let M be a closed, orientable, irreducible, geometrizable 3-manifold. We prove that the profinite topology on the fundamental group of π 1 (M ) is efficient with respect to the JSJ decomposition of M . We go on to prove that π 1 (M ) is good, in the sense of Serre, if all the pieces of the JSJ decomposition are. We also prove that if M is a graph manifold then π 1 (M ) is conjugacy separable.A group G is conjugacy separable if every conjugacy class is closed in the profinite topology on G. This can be thought … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(74 citation statements)
references
References 33 publications
(56 reference statements)
3
69
0
Order By: Relevance
“…This complements a result by Wilton and Zalesskii [WiltZa10] who showed that every graph manifold group G is good in the sense of Serre [Se97, Section 2.6, exercises], that is, with G denoting the profinite completion of G, for every finite G-module M and n ≥ 1, the natural morphism G → G induces an isomorphism H Lemma 5.11. Suppose G is a p-efficient graph of finitely generated groups with underlying graph Y and fundamental group G = π 1 (G).…”
Section: Cohomological P-completenesssupporting
confidence: 80%
See 2 more Smart Citations
“…This complements a result by Wilton and Zalesskii [WiltZa10] who showed that every graph manifold group G is good in the sense of Serre [Se97, Section 2.6, exercises], that is, with G denoting the profinite completion of G, for every finite G-module M and n ≥ 1, the natural morphism G → G induces an isomorphism H Lemma 5.11. Suppose G is a p-efficient graph of finitely generated groups with underlying graph Y and fundamental group G = π 1 (G).…”
Section: Cohomological P-completenesssupporting
confidence: 80%
“…It seems plausible that this result might play the same role in studying the (virtual) conjugacy p-separability of graph manifold groups as finite efficiency does in the proof of their conjugacy separability, which was also established in [WiltZa10]. We do not pursue this issue further in the present paper; however, we note that Proposition 3 also implies that virtually, the fundamental group of a closed graph manifold group and its pro-p completion have the same mod p cohomology in a certain sense, explained in Section 5.2.…”
Section: Graph Manifoldsmentioning
confidence: 59%
See 1 more Smart Citation
“…Note that an amalgamated free product is a special case of this situation, namely corresponding to the case when Γ consists of one edge and two vertices. The next proposition from [22] collects (from [17]) some useful facts about group actions on profinite trees and will be used frequently in this paper. We note however that it does not need full strength of the hypothesis there, but only the embedding S(G) into S(  G) that in turn follows from closedness of vertex and edge groups in the profinite topology.…”
Section: Suppose G Is Conjugacy Separable and Let H ≤ G Be A Subgroupmentioning
confidence: 99%
“…(4) Lemma 5.3 is in the spirit of a result of Wilton and Zalesskii [49], where it is proved that fundamental groups of the vertex manifolds in the JSJ decomposition are separable.…”
Section: Remarksmentioning
confidence: 99%